2018
DOI: 10.1021/acs.macromol.8b01564
|View full text |Cite
|
Sign up to set email alerts
|

Wear-Induced Microstructural and Chemical Changes in Poly[tetrafluoroethylene-co-(perfluoroalkyl vinyl ether)] (PFA)

Abstract: Friction-induced shear stress and wear of poly [tetrafluoroethylene-co-(perfluoroalkyl vinyl ether)], also known as perfluoroalkoxy polymer (PFA), causes microstructural and chemical changes. These changes are essential to understand PFA as a tribological material. Tribological (friction and wear) experimentation coupled with differential scanning calorimetry, X-ray diffraction, and infrared spectroscopy was used to characterize the microstructure and chemical differences in PFA wear debris versus bulk. PFA we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…28,29,36,39,40 It has been demonstrated that the tribochemical breaking of C−C bonds in the PTFE backbone occurs in non-ultralow wear PTFE systems, and even unfilled PTFE and perfluoroalkoxy polymer (a random copolymer of TFE and a few mol % of perfluoroalkyl vinyl ether). 61,62 It is hypothesized that tribochemically generated carboxyl/carboxylic acid end groups are not unique to ultralow wear PTFE; they are expected to form in higher wearing PTFE composites and unfilled PTFE but only accumulate measurably (via IR) in the tribofilms of the ultralow wear composites. This occurs because conditions for ultralow wear PTFE promoted extended shearing cycles on the same region of the polymer, which created progressively more carboxylic acid end groups that bond to nearby metallic surfaces to form protective films.…”
Section: Resultsmentioning
confidence: 99%
“…28,29,36,39,40 It has been demonstrated that the tribochemical breaking of C−C bonds in the PTFE backbone occurs in non-ultralow wear PTFE systems, and even unfilled PTFE and perfluoroalkoxy polymer (a random copolymer of TFE and a few mol % of perfluoroalkyl vinyl ether). 61,62 It is hypothesized that tribochemically generated carboxyl/carboxylic acid end groups are not unique to ultralow wear PTFE; they are expected to form in higher wearing PTFE composites and unfilled PTFE but only accumulate measurably (via IR) in the tribofilms of the ultralow wear composites. This occurs because conditions for ultralow wear PTFE promoted extended shearing cycles on the same region of the polymer, which created progressively more carboxylic acid end groups that bond to nearby metallic surfaces to form protective films.…”
Section: Resultsmentioning
confidence: 99%
“…The second heating cycle (Figure 3) shows an endotherm peak, in the range of −10–10 °C, which corresponds to the solid−solid transition of PFA crystallites from the triclinic to hexagonal crystalline structure. [ 12 ] This transition can be attributed to greater molecular mobility of the PFA side chain, due to the oxygen present in the structure, which allows a rearrangement in the crystal in the transition region between the crystal and amorphous phase during heating or cooling.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, research efforts were trying to modify PTFE in different ways to overcome these shortcomings, because modified PTFE significantly reduced melt viscosity by lowering the crystallinity through the incorporation of bulky comonomers [11] into the polymer main chain. [6] In this way, copolymerizing perfluoroalkyl vinyl ether with PTFE led to tetrafluoroethylene-perfluoroalkyl vinylether copolymer (PFA) (Figure 1b), which exhibit reduced crystallinity, [12] lower melting points and making the polymer easier to process. [13] The consumption of fluoropolymers has increased over the last decade, as technological advancement has required their unique properties in several applications, ranging from the biomedical and aerospace industry to everyday household appliances.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of low temperature on transfer film formation is controversial, as shown in figure 5(b). The formation of a transfer film is strongly related to tribochemical reactions such as chain section, chelating reaction between carboxylic group and metal substrate, as well as structure orientation, among others [112,113,[122][123][124][125][126]. Transfer films strongly adhere to the counterface and have low shearing force.…”
Section: Transfer Film and Tribochemistrymentioning
confidence: 99%